The Role of the Total Physical Response (TPR) Method in Improving Arabic Vocabulary Mastery for Prayer Recitations/Peran Metode Total Physical Response (TPR) dalam Meningkatkan Penguasaan Kosakata Bahasa Arab Bacaan Shalat - Nova Aulia; Talqis Nurdianto; Najmatuzzahiroh Najmatuzzahiroh (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2025)
This research examines the effectiveness of the Total Physical Response (TPR) method in improving Arabic Vocabulary mastery for prayer recitations among elementary school students. Using a quantitative quasi-experimental design. The subjects research were 56 third-grade students from the Indonesian school in Mecca, divided into two groups: 28 students in the experimental group and 28 students in the control group, selected by stratified random sampling. The data were collected using Arabic vocabulary tests, administered before and after the training, and then analysed using IBM SPSS Statistics 27 through assumptions (normality and homogeneity) and hypothesis tests (independent sample t-test). After the test, a significant difference of p=0.006 (p < 0.05) was found in the independent sample t-test, which supported the normal distribution and homogeneity of variance. These findings indicate that the TPR method is an effective, engaging, and contextual approach to enhancing Arabic vocabulary learning for prayer recitations. This novelty highlights the potential of TPR to faster both language mastery and religious comprehension among elementary learners in an Islamic educational.Penelitian ini untuk menguji efektivitas metode Total Physical Response (TPR) dalam meningkatkan penguasaan kosakata Bahasa Arab untuk bacaan salat di kalangan siswa sekolah dasar. Menggunakan metode kuantitatif dengan desain kuasi-eksperimental. Subjek yang diteliti adalah 56 siswa kelas tiga di Sekolah Indonesia Mekkah, dibagi menjadi dua kelompok: 28 siswa dalam kelompok eksperimen dan 28 siswa dalam kelompok kontrol, dipilih secara stratified random sampling. Data dikumpulkan menggunakan tes kosakata bahasa Arab, yang diberikan sebelum dan sesudah pelatihan, dan kemudian dianalisis menggunakan IBM SPSS Statistics 27 melalui asumsi (normalitas dan homogenitas) dan uji hipotesis (uji-t independen sampel). Setelah uji coba, perbedaan signifikan p=0,006 (p < 0,05) ditemukan pada uji-t sampel independen, yang mendukung distribusi normal dan homogenitas varians. Temuan ini menunjukkan bahwa metode TPR merupakan pendekatan yang efektif, menarik, dan kontekstual untuk meningkatkan pembelajaran kosakata bahasa Arab dalam bacaan salat. Hal baru ini menyoroti potensi TPR untuk mendorotong penguasaan bahasa dan pemahaman di kalangan pelajar sekolah dasar dalam konteks pendidikan Islam.